Digitalisasi dan Implementasi 5S (Seiri, Seiso, Seiton, Seiketsu, Shitsuke) pada UMKM Jenang Aliya Kudus - Supriyanto, Agus; Lukas, Ahmad; N.A, Alfiyatun Nida'; Najiha, Nuhayatun; Alfisyahr, Layli Noor; Hikmah, Nurul; Sutrisno, Sutrisno; Aziz, M. Abdul; Khoiriyah, Nur (Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
The purpose of the service program being implemented is to provide training on the use of information technology to market products from UMKM Jenang Aliya Kudus. Marketing that is carried out is still conventional and the absence of social media from products from MSME Jenang Aliya makes these products not widely known by netizens. The result of the implementation of this service program is that MSME actors know the importance of using digital technology to introduce and market their products to the wider community. Because Kudus, besides being known as the city of kretek, is also known for its jenang souvenirs. This service program is carried out by introducing products to netizens through creating addresses on a google map, creating social media accounts starting from Facebook, Twitter and Instagram. Meanwhile, the implementation of 5S (Seiri, Seiso, Seiton, Seiketsu, Shitsuke) is carried out so that the work place and environment become tidier, cleaner, and organized according to their classification.